Bullying di Sekolah dalam Perspektif Interaksionisme Simbolik - Samsul Ma'arif; M Toha Hidayatulloh; Sahid Nur Aziz; Kamilatus Syarifah (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2026)
Bullying in schools remains a significant social issue that affects students' psychological, social, and academic development. This study aims to analyze bullying phenomena in schools through the perspective of symbolic interactionism. The research positions bullying as a social construct formed through interaction, interpretation, and the exchange of meanings among students. This study employed a qualitative literature review approach by examining relevant journals, books, and scientific publications concerning bullying and symbolic interactionism. The findings indicate that bullying appears in verbal, physical, social, and cyber forms. These behaviors are sustained through social meanings, labeling processes, and power relations within peer groups. Negative labeling influences victims' self-concept, confidence, social relationships, and learning motivation. The study also highlights the important role of teachers and schools in preventing bullying through supervision, supportive communication, and character education programs.